Guía metodológica de gestión de proyectos de incorporación de nuevos productos para medianas empresas del sector comercio de la Región Central Occidental de Costa Rica - Calderón-Marín, Álvaro; Ocampo-Hernández, Bárbara (Instituto Tecnológico de Costa Rica, 2016)
This paper was performed in a selected group of seven medium enterprises (SMEs) from the commercial sector of Middle-Western Region of Costa Rica with the purpose to generate a project management methodology for new product introduction. For that reason, the strengths and weaknesses of these companies in project management were identified. The main problems detected were related to Time, Resources and Risk Subjects. Additionally, it is important to mention that based on the commercial approach of this companies the development of the Procurement Subject is a critical aspect. The standard ISO 21500:2012 and the requirements of the SMEs were taken in consideration for creating an adapted the project management methodology. Each of the subjects of the ISO 21500 were analyzed; as result the Integration and Quality subjects were complete removed and specific processes from other subjects were also eliminated. Finally, the evaluated processes were combined in order to create new four subjects: Definition, Time and Cost; Resources Management; Procurement Management and Risk Management. Each new subject have their own and unique processes that are linked to the respective tools and templates. The final result is a manual with tools and templates that represent an innovative, simplified and value added solution for covering the project management requirements of the selected companies.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, Escuela de Ingeniería en Computación, Escuela de Administración de Empresas, 2016.
Keywords: PYME; Comercio; PMBoK®; ISO 21500; PRINCE2®